Topics in Regional Anesthesia - Whizar-Lugo, Víctor M.; Ramón Saucillo-Osuna, José; Castorena-Arellano, Guillermo (IntechOpen, 2022)
Regional anesthesia has progressively evolved and currently occupies a predominant place in our daily practice. The development of skills for the safe practice of regional anesthesia requires in-depth knowledge of anatomy, physiology, pharmacology, and the pathology of each patient candidate to receive some type of regional block, as well as special and prolonged training beyond residence, particularly in this era of the COVID-19 pandemic, during which the training of thousands of anesthesiology residents has been impaired. Undoubtedly, the benefits of regional anesthesia techniques are enormous, as are their complications. Countless guidelines for regional anesthesia have been described based on the classic anatomical recommendations, the search for paresthesias, neurostimulation, and medical images. The introduction of ultrasound guidance and the rational use of local anesthetics and their adjuvants have favorably revolutionized regional anesthesia, making it safer and more effective. This book addresses several contemporary topics in regional anesthesia in a variety of interesting clinical settings with practical importance.